Social spending generosity and income inequality: a dynamic panel approach - Judith Niehues (Institute for the Study of Labor (IZA), 2010)
This paper explores if more generous social spending polices in fact lead to less income inequality, or if redistributive outcomes are offset by behavioral disincentive effects. To account for the inherent endogeneity of social policies with regard to inequality levels, I apply the System GMM estimator and use the presumably random incidence of certain diseases as instruments for social spending levels. The regression results suggest that more social spending effectively reduces inequality levels. The result is robust with respect to the instrument count and different data restrictions. Looking at the structure of benefits, particularly unemployment benefits and public pensions are responsible for the inequality reducing impact. More targeted benefits, however, do not significantly reduce income inequality. Rather, their positive effect on pre-government income inequality hints at substantial disincentive effects.
Keywords: D31; D60; H20; 330; social benefits; redistribution; income inequality; System GMM; Sozialhilfe; Sozialtransfer; Öffentliche Sozialausgaben; Einkommensumverteilung; Wirkungsanalyse; Verteilungswirkung; Einkommensverteilung; Schätzung; Gini-Koeffizient; EU-Staaten